2012
DOI: 10.1016/j.ajpath.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin(ogen)-Independent Role of Plasminogen Activators in Acetaminophen-Induced Liver Injury

Abstract: Hepatic fibrin(ogen) has been noted to occur after acetaminophen (APAP)-induced liver injury in mice. Deficiency in plasminogen activator inhibitor-1 (PAI-1), an endogenous inhibitor of fibrinolysis, increases APAP-induced liver injury in mice. However, the roles of fibrinogen and fibrinolysis in APAP-induced liver injury are not known. We tested the hypothesis that hepatic fibrin(ogen) deposition reduces severity of APAP-induced liver injury. APAP-induced (300 mg/kg) liver injury in mice was accompanied by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(82 citation statements)
references
References 31 publications
4
76
1
Order By: Relevance
“…The role of PAI-1 in models of liver injury and disease has been extensively studied. For example, PAI-1 deficiency increases liver injury in models of acetaminophen and carbon tetrachloride hepatotoxicity (von Montfort et al, 2010;Sullivan et al, 2012b). In agreement with our finding that inhibition of fibrinolysis with TA reduces ANIT-mediated liver injury and fibrosis, we found that PAI-1 deficiency increased ANIT diet-induced liver injury and fibrosis.…”
Section: Antifibrinolytic Therapy Reduces Liver Injury and Fibrosissupporting
confidence: 81%
See 3 more Smart Citations
“…The role of PAI-1 in models of liver injury and disease has been extensively studied. For example, PAI-1 deficiency increases liver injury in models of acetaminophen and carbon tetrachloride hepatotoxicity (von Montfort et al, 2010;Sullivan et al, 2012b). In agreement with our finding that inhibition of fibrinolysis with TA reduces ANIT-mediated liver injury and fibrosis, we found that PAI-1 deficiency increased ANIT diet-induced liver injury and fibrosis.…”
Section: Antifibrinolytic Therapy Reduces Liver Injury and Fibrosissupporting
confidence: 81%
“…As a hemostatic agent, TA is reported to have a favorable safety profile for existing indications Muse et al, 2011) and has been demonstrated as an inexpensive and effective treatment for traumatic bleeding, as suggested recently by the multicenter Clinical Randomization of an Antifibrinolytic in Significant Hemorrhage-2 trial (Roberts et al, 2011). In agreement with our findings in plasminogen-null mice, administration of TA also attenuated acetaminophen hepatotoxicity in mice, albeit to a lesser extent (Sullivan et al, 2012b). However, the impact of TA treatment on chronic liver injury has not been broadly investigated in humans or animal models.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Pharmacological inhibition or genetic depletion of the plasmin zymogen plasminogen significantly reduces APAP-induced liver damage in mice (38). Conversely, hepatic fibrosis, necrosis, and hemorrhage are enhanced in APAP-treated mice with a global PAI-1 deficiency (38).…”
Section: Discussionmentioning
confidence: 99%